2021
DOI: 10.1002/ctm2.503
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic PAX6 elicits CDK4/6 inhibitor resistance by epigenetically inactivating the LATS2‐Hippo signaling pathway

Abstract: Intrinsic resistance to CDK4/6 inhibitors hinders their clinical utility in cancer treatment. Furthermore, the predictive markers of CDK4/6 inhibitors in gastric cancer (GC) remain incompletely described. Here, we found that PAX6 expression was negatively correlated with the response to palbociclib in vitro and in vivo in GC. We observed that the PAX6 expression level was negatively correlated with the overall survival of GC patients and further showed that PAX6 can promote GC cell proliferation and the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Hippo Signaling Pathway. Oncogenes often promote tumor progression by regulating the signaling pathways [12,13]. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that TOP2A was associated to cell cycle, progesterone-mediated oocyte maturation, p53 signaling pathway, and Hippo signaling pathway (Figure 5(a)).…”
Section: Top2a Affecting Hcc Tumor Progression Throughmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippo Signaling Pathway. Oncogenes often promote tumor progression by regulating the signaling pathways [12,13]. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that TOP2A was associated to cell cycle, progesterone-mediated oocyte maturation, p53 signaling pathway, and Hippo signaling pathway (Figure 5(a)).…”
Section: Top2a Affecting Hcc Tumor Progression Throughmentioning
confidence: 99%
“…Dysregulation of the Hippo signaling pathway promotes cancer progression [ 12 , 13 ]. Moya et al [ 14 ] found that the activity of yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) in tumors was linked to the progression of liver tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, LATS2 12 suppresses cancer progression through maintaining cell identity and metabolic state [41]. LATS2 also participates in gastric cancer proliferation and invasion [42,43]. This study found that LATS2 was down-regulated in gastric cancer.…”
Section: Discussionmentioning
confidence: 84%
“…It plays a critical role in centrosome duplication, mitotic delity, and genomic stability, and negatively regulates the G1/S transition by reducing cyclin E/CDK2 kinase activity. Here, we found dysregulation of Hippo after depletion of LEF1 and KDM4A, and noticed that LATS2 regulated multiple downstream targets associated with cell cycle and apoptosis [48,49]. After knockdown of LEF1 or KDM4A, the cell cycle was stalled at the G1 phase [17,50], which may be due to the increased level of LATS2.…”
Section: Discussionmentioning
confidence: 99%